The Buddies In a Day For Knights - Bluth, Brad. frey50; Bluth, Toby (Milwaukee, Wis. : Ideals Pub. Corp., 1984)
Three friends, as knights of old, rescue a baby egg from a terrible fate.
Spine title: A day for knights.
74555
Keywords: Children's stories, American; Friendship -- Fiction; Stories in rhyme